Effectiveness of the “My Body Belongs to Me” Pop-Up Book on Preschool Children’s Understanding of Body Safety - Maria Ulfah Kurnia Dewi; Ismi Elya Wirdati; Dewi Puspitaningrum; Nuke Devi Indrawati; Vilda Hiktiawati; Nur Safika; Ellyzabeth Sukmawati (MEDICA (International Medical Scientific Journal), 2026)
Child sexual violence is a major public health concern, emphasizing the need for developmentally appropriate body safety education during early childhood. This study aimed to evaluate the effectiveness of the My Body Belongs to Me Pop-Up Book in improving preschool children's understanding of body safety. A quasi-experimental pretest-posttest control-group study was conducted among 60 preschool children at Al Huda Kindergarten, Semarang, Indonesia. Participants were assigned to an intervention group receiving body safety education through the My Body Belongs to Me Pop-Up Book or a control group receiving conventional leaflet-based education. Children's understanding was assessed using a 10-item picture-based Situational Judgment Test. Data were analyzed using independent-samples and paired-samples t-tests, with Cohen's d used to estimate effect size. Baseline understanding did not differ significantly between groups (p = 0.076). After the intervention, the intervention group achieved significantly higher posttest scores than the control group (8.37 ± 1.40 vs. 5.73 ± 1.11; p < 0.001), with a very large effect size (Cohen's d = 2.08). Significant improvement was observed only in the intervention group (p < 0.001). The My Body Belongs to Me Pop-Up Book was more effective than leaflet-based education in improving preschool children's understanding of body safety, supporting its use as an interactive and developmentally appropriate educational tool for early child sexual violence prevention.